STUDI KOMPARATIF KINERJA KEUANGAN PADA PERUSAHAAN DOMESTIK DAN PERUSAHAAN MULTINASIONAL DI BURSA EFEK INDONESIA - Tiasita, Ni Kadek Meida; Wiagustini, Luh Putu (E-Jurnal Manajemen, 2017)
This study aims to explain how the significance of differences in financial performance of domestic company and multinational corporations of manufacturing sector listed in Indonesia Stock Exchange in 2013 - 2015. The financial performance is measured by the five financial ratios derived from the annual financial statements of the company which is liquidity ratio, activity ratio, solvency ratio, profitability ratio and market value ratio. This research sample as many as 50 domestic companies and 50 multinational companies obtained through multistage purposive sampling method. This study uses Independent Sample T-Test as its analysis technique. The results showed that there is no significant difference in financial performance of domestic companies and multinational corporations. It can be seen that the average for each ratio in the domestic and  multinational company from year to year is not much different.
Keywords: financial performance, financial ratios, domestic corporation, multinational corporation